2016
DOI: 10.1080/07352689.2016.1172461
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Is a Language of Chemical Signals and Plays an Ecological Role in Algal-Bacterial Interactions

Abstract: Algae are ubiquitous in the marine environment, and the ways in which they interact with bacteria are of particular interest in marine ecology field. The interactions between primary producers and bacteria impact the physiology of both partners, alter the chemistry of their environment, and shape microbial diversity. Although algal-bacterial interactions are well known and studied, information regarding the chemical-ecological role of this relationship remains limited, particularly with respect to quorum sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(72 citation statements)
references
References 243 publications
(204 reference statements)
2
68
1
1
Order By: Relevance
“…Vibrios share the aquatic environment with (micro)algae, and both groups of organisms are known to interact with each other in various ways (ranging from mutualistic to antagonistic) (Mayali and Azam, 2004;Amin et al, 2015). While these interactions are most likely coordinated by signalling mechanisms between bacteria and algae, little is known with respect to signalling mechanisms that occur between algae and bacteria (Zhou et al, 2016). Interestingly, various (micro)algae produce indole analogues such as indole-3-acetic acid and indole-3-acetamide (Supporting Information Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrios share the aquatic environment with (micro)algae, and both groups of organisms are known to interact with each other in various ways (ranging from mutualistic to antagonistic) (Mayali and Azam, 2004;Amin et al, 2015). While these interactions are most likely coordinated by signalling mechanisms between bacteria and algae, little is known with respect to signalling mechanisms that occur between algae and bacteria (Zhou et al, 2016). Interestingly, various (micro)algae produce indole analogues such as indole-3-acetic acid and indole-3-acetamide (Supporting Information Fig.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the ecological distribution and potential functions of AHL-producing microbes in plant field have also garnered much attention. AHL signaling has been shown to play a role in the manifestation of the plant-associated phenotypes of numerous autotrophic, pathogenic, and symbiotic bacterial strains (Chong et al, 2012; van Dam and Bouwmeester, 2016; Zhou et al, 2016). A recent study demonstrated that AHL-producing Alpha-proteobacteria participated in nitrogen-cycling in legumes plant soil (Venturi and Keel, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Violacein was also detectable in the planktonic biomass of both cultures but was present in greater quantity in the cotton‐associated biomass as seen in Supporting Information Figure S4. As described in the Introduction, it has previously been reported that violacein biosynthesis in Pseudoalteromonas is regulated by quorum sensing molecules including acyl‐homoserine lactones (Wang et al., ) , and there is an‐established interdependency of quorum sensing and epibiotic biofilm formation in marine bacteria (Zhou et al., ). Our SEM images and UPLC‐MS data taken together confirm that the presence of the cotton is facilitating biofilm formation and violacein biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that biofilm formation and quorum sensing are intimately linked for many microbes; however, there are multiple instances where secondary metabolite production is also altered as a result of these behaviors. (Atkinson, Cámara, & Williams, 2007;Barnard et al, 2007;Beauvais & Latgé, 2015;Bleich, Watrous, Dorrestein, Bowers, & Shank, 2015;Braga, Dourado, & Araujo, 2016;Busetti, Maggs, & Gilmore, 2016;Cude & Buchan, 2013;Cude et al, 2015;Favre et al, 2017;Harrington et al, 2014;Johnson, Kido Soule, & Kujawinski, 2016;Nickzad & Déziel, 2013;Othmani, Briand, Ayé, Molmeret, & Culioli, 2016;Zhou, Lyu, Richlen, Anderson, & Caia, 2016). For example, regulation of the biosynthesis of violacein, an antibacterial secondary metabolite produced by several species of Pseudoalteromonas, is highly sensitive to acyl-homoserine lactone (AHL) quorum sensing (Ayé et al, 2015;Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%